Congenital Malaria due to Plasmodium Vivax Infection in a Neonate - Ravi Bhatia; Dinesh Rajwaniya; Priti Agrawal (Hindawi Limited, 2016)
Although malaria is endemic in India, congenital malaria is not very common. Congenital malaria is a very rare condition in both endemic and nonendemic areas. We report a case of congenital malaria in a six-day-old neonate with fever and splenomegaly. The diagnosis was picked up accidentally on a peripheral smear examination. Congenital malaria should be kept as differential diagnosis of neonatal sepsis. Timely detection of this condition could lead to early diagnosis and treatment, thereby preventing neonatal mortality.